2018
DOI: 10.1177/1203475418814234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Management Guidelines for Moderate-to-Severe Plaque Psoriasis: A Review of Phototherapy, Systemic Therapies, and Biologic Agents

Abstract: Introduction: Many international guidelines for management of psoriasis exist and most have variations in grading evidence quality, strength of recommendations, and dosing. The objective of our review is to compare international guidelines published in the United Kingdom, Canada, Europe, and the United States for the management of moderate-to-severe plaque psoriasis. Methods: We conducted a literature review on systemic therapies and phototherapy for moderate-to-severe plaque psoriasis in adult patients. The B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…Psoriasis is a systemic inflammatory disease characterized by a growing body of comorbidities; however availability of targeted anti‐psoriatic therapy has been largely limited (Al‐Mutairi, Al‐Farag, Al‐Mutairi, & Al‐Shiltawy, ; Asa'ad, Fiore, Alfieri, et al, ; Fiore, Leone, Maraolo, et al, ; Jiang, Hinchliffe, & Wu, ; Santus, Rizzi, Radovanovic, et al, ; Yadav, Singh, & Singh, ). More recently, clinicians have been able to better treat psoriasis due to the development of targeted therapy allowing for: (a) second‐step therapy in moderate to severe psoriasis, (b) treatment of moderate to severe psoriasis in patients which have contraindication for traditional systemic drugs and/or (c) treatment of mild psoriasis not responsive to topical treatments (Ighani et al, ). One of the more recently approved targeted therapies is the new Interleukin (IL)‐17 inhibitors (i).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a systemic inflammatory disease characterized by a growing body of comorbidities; however availability of targeted anti‐psoriatic therapy has been largely limited (Al‐Mutairi, Al‐Farag, Al‐Mutairi, & Al‐Shiltawy, ; Asa'ad, Fiore, Alfieri, et al, ; Fiore, Leone, Maraolo, et al, ; Jiang, Hinchliffe, & Wu, ; Santus, Rizzi, Radovanovic, et al, ; Yadav, Singh, & Singh, ). More recently, clinicians have been able to better treat psoriasis due to the development of targeted therapy allowing for: (a) second‐step therapy in moderate to severe psoriasis, (b) treatment of moderate to severe psoriasis in patients which have contraindication for traditional systemic drugs and/or (c) treatment of mild psoriasis not responsive to topical treatments (Ighani et al, ). One of the more recently approved targeted therapies is the new Interleukin (IL)‐17 inhibitors (i).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in accordance with recent meta‐analyses, studies and guidelines, TNF inhibitors such as infliximab and adalimumab have been reported to be the most effective drugs prescribed in the presence of PsA and moderate‐to‐severe disease condition. This prescription was also observed at baseline in our semantic map.…”
Section: Discussionmentioning
confidence: 57%
“…The same was true for etanercept that was linked to CKD and TBC. Etanercept, ustekinumab and secukinumab were all connected to a complex history of previous systemic treatments for psoriasis (two or more), moderate disease condition (PASI: [10][11][12][13][14][15][16][17][18][19][20], overweight and university education.…”
Section: Semantic Mapmentioning
confidence: 99%
See 2 more Smart Citations